Synthesis, Biological and Thermal Properties of Schiff bases of Bisphenol-C - Karia, F.D.; Parsania, P.H. (Asian Journal of Chemistry, 2010)
Schiff bases based on bisphenol-C were synthesized by reacting substituted benzaldehyde (o-NO2, p-NO2 and p-OCH3) and amino bisphenol-C in DMF. The structures are supported by UV, IR and NMR spectral data. The schiff bases showed promising antibacterial and antifungal activities against E. coli and A. awamori and moderate activities against B. mega. BSB-3 has excellent thermal stability (662ºC) while MSB-2 has least thermal stability (188ºC) and the rest have comparatively good thermal stability.